SHA-512 Algorithm on Json Web Token for Restful Web Service-Based Authentication - Rasyada, Naufal (Journal of Applied Data Sciences, 2022)
The development of technology is getting faster and continues to grow so as to create various types of technology, architecture, to new programming languages. Surely this will be a new problem because of differences in technology, programming language, and architecture that must still be able to provide interconnected sources of information. So in order for the system to remain integrated, a Web Service (WS) is needed as a bridge in integrating between systems without differentiating the platform, programming language, or architecture used. One of the Web Service architectures that is widely used is REST (REpresentational State Transfer), but there will be problems in implementing REST Web Service because it does not have security standards in the authentication process. Then an authentication method is needed, namely JSON Web Token (JWT). In implementing JWT, a hash algorithm is needed, such as SHA-512. The results of this study indicate that the use of SHA-512 on the JWT has a good speed with an average data request speed of 512.8 milliseconds (ms) when compared to the SHA-256 algorithm which has an average data request speed of 515.55 MS. Meanwhile, in terms of data size, SHA-512 produces an average data request size of 0.75 kilobytes (kb) compared to SHA-256 which has an average data request size of 0.72 kb.